Redistributive Politics, Power Sharing and Fairness - Dario Debowicz; Alejandro Saporiti; Yizhi Wang (Luxembourg Income Study (LIS), 2016)
We study the effect of power sharing over income redistribution among different socio-economic groups in a model of redistributive politics with fairness concern. We prove that a unique pure-strategy equilibrium exists under fairly general conditions; and we show that equilibrium transfers depend on the interplay of four main factors: (i) the gap between the population and the group average pre-tax income; (ii) the relative ideological neutrality of the poor, (iii) parties' and voters' concern with income inequality, and (iv) the proportionality of the electoral rule. A number of comparative statics predictions emerge from our characterization. Among them, our analysis shows that the net transfers to the middle class and the rich (resp., the poor) increase (resp., decrease) with power sharing disproportionality. Further, we prove that the Gini coefficient associated with the distribution of disposable incomes also rises with the disproportionality of the power sharing rule, which amount to say that income inequality rises as policymaking power gets more concentrated in the majority winning party. We confront these predictions to the data, using an unbalanced panel of developed and developing democracies. The empirical evidence strongly supports both, the positive effect of the income gap over the group transfers, and the relationship between the Gini index (and respectively, the group transfers) and power sharing disproportionality.
Keywords: C72; D72; D78; 330; Income Redistribution; Targeted Spending; Swing Voter; Electoral Rule; Power Sharing; Fairness; Income Inequality